Prevalence and Risk Factors of Bovine Trypanosomiasis in Khartoum State, Sudan, April-July 2012 (Global Journal of Medical Research, 2019)
A cross-sectional study was conducted in the dry season from April to July 2012 in Khartoum State, Sudan to: estimate the prevalence of bovine trypanosomiasis (BT), identify the prevailing species of trypanosomes and investigate the associated potential risk factors of the disease. Blood samples were collected from 271 randomly selected cattle of the eight study areas and evaluated through standard parasitological methods (Haematocrit Centrifugation Technique (HCT) and thin blood smear). Also, the packed cell volume (PCV) of each animal was measured using Haematocrit Techniques for anemia estimation. The results indicated that the overall prevalence of BT was 4.8% (13/271). All the trypanosomes encountered in cattle belonged to a single species of Trypanosoma vivax. For investigation of associated risk factors of the disease, a univariate analysis using the Chi-square (χ 2 ) test identified 15 risk factors statistically significantly associated with BT (p ≤ 0.25). These 15 risk factors were entered to the multivariate analysis using logistic regression for further analysis. The significant level of association in the multivariate analysis was set at (p≤ 0.05).
Keywords: prevalence; risk factors; cattle; trypanosome- vivax; Khartoum state; sudan